TINDAK TUTUR KOMISIF DALAM FILM THE CONJURING 2 KARYA CHAD HAYES (SUATU ANALISIS PRAGMATIK) - Koraag, Yoanita Angela; Lasut, Theresia M.C; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
ABSTRACT                                               Yoanita Angela Koraag1                                       Dra. Theresia M. C. Lasut, M.Hum2                                     Donald Ringgo Lotulung, S.S M.Hum3     This research is entitled "Tindak Tutur Komisif dalam film The Conjuring 2. This study aims to identify, classify, and analyze the kinds and functions of commissive act in the film The Conjuring 2. This study used a descriptive method. Data were collected from conversations between characters, then classified and analyzed according to Austin's (1962) theory. Austin divided speech acts into three categories, namely locutionary acts, illocutionary acts and perlocutionary acts. Austin then classifies utterances according to the meaning of the illocutionary, namely verdictive, executive, commissive, behabitive, and expositive. There are twenty six kinds of commissive act in The Conjuring 2 movie by Chad Hayes, those are promise, declare for, undertake, intend, guarantee, bet, engage, agree, purpose, contract, vow, adopt, mean to, envisage, dedicate myself to, am determined to, covenant, bind, plan, propose to, espouse, shall, oppose, contemplate, consent and side with. The functions that have been found are commissive act intending, commissive act promising, commissive act declaring, commissive act vowing, commissive act undertaking, commissive act purposing, commissive act guaranteeing, commissive act meaning to, commissive act agreeing, commissive act engaging, commissive act opposing, while functions like betting, contracting, adopting, envisaging, dedicate myself to, am determined to, covenanting, binding, planning, proposing, espousing, shall, contemplating, consenting and siding with were not found in The Conjuring 2 movie._ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _Keywords: Commissive Act, Film The Conjuring 2, Pragmatic Analysis